Pharmacological Modulation of Neurite Outgrowth in Human Neural Progenitor Cells by Inhibiting Non-muscle Myosin II - Lilienberg, Julianna; Hegyi, Zoltán; Szabó, Eszter; Hathy, Edit; Málnási-Csizmadia, András; Réthelyi, János M.; Apáti, Ágota; Homolya, László (Frontiers in Cell and Developmental Biology, 2021)
Studies on neural development and neuronal regeneration after injury are mainly based on animal models. The establishment of pluripotent stem cell technology, however, opened new perspectives for better understanding these processes in humans by providing unlimited cell source for hard-to-obtain human tissues. Here, we aimed at identifying the molecular factors that confine and modulate an early step of neural regeneration, the formation of neurites in human neural progenitor cells (NPCs). Enhanced green fluorescent protein (eGFP) was stably expressed in NPCs differentiated from human embryonic and induced pluripotent stem cell lines, and the neurite outgrowth was investigated under normal and injury-related conditions using a high-content screening system. We found that the non-muscle myosin II (NMII) inhibitor blebbistatin and its novel, non-toxic derivatives initiate extensive neurite outgrowth in human NPCs. We observed that the extracellular matrix components greatly influence the rate of neurite formation, but NMII inhibitors are able to override the inhibitory effect of the restrictive environment. Similar, non-additive stimulatory effect on neurite generation was detected by the inhibition of ROCK1 kinase, the upstream regulator of NMII, whereas inhibition of JNKs had negligible effect, suggesting that ROCK1 signal is dominantly manifested by the actomyosin activity. In addition to providing a reliable cell-based in vitro model for identifying intrinsic mechanisms and environmental factors responsible for impeded axonal regeneration in humans, our results demonstrate that NMII and ROCK1 are important pharmacological targets for the augmentation of neural regeneration at the progenitor level, and may open novel perspectives for development of more effective pharmacological and cell therapies for various neurodegenerative disorders.